2019
DOI: 10.1177/0014402919872688
|View full text |Cite
|
Sign up to set email alerts
|

The GRE and Students With Disabilities: A Validity Study at 10 Universities

Abstract: We evaluated the validity of using the GRE General Test to assist with graduate school admissions for individuals with disabilities. We studied a sample of 16,239 graduate students from 10 U.S. research universities in three groups: students without any reported disabilities, students who reported disabilities and took the computer-delivered GRE with accommodations, and students who reported disabilities but took the computer-delivered GRE without accommodations. We examined differential prediction using multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Specifically focusing on Deaf as a student with disabilities, there is limited research on GRE and students with disabilities, and most of the studies that focused on testing college entry exams such as GRE and SAT taken by applicants with disabilities occurred almost 40 years ago (Benet et al, 1984 ; Benet et al, 1985 ; Braun et al, 1986 ; Ragosta & Kaplan, 1986 ; Ragosta & Nemceff, 1982 ). A more recent survey examined the predictive ability of GRE scores for graduate students with disabilities compared to those without disabilities (Ling et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically focusing on Deaf as a student with disabilities, there is limited research on GRE and students with disabilities, and most of the studies that focused on testing college entry exams such as GRE and SAT taken by applicants with disabilities occurred almost 40 years ago (Benet et al, 1984 ; Benet et al, 1985 ; Braun et al, 1986 ; Ragosta & Kaplan, 1986 ; Ragosta & Nemceff, 1982 ). A more recent survey examined the predictive ability of GRE scores for graduate students with disabilities compared to those without disabilities (Ling et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study concurred with the previous research findings that there was a significant difference between students with disabilities and those without disabilities. Ling et al, ( 2020 ) showed that the significant difference between students with and without disabilities was on GRE Quantitative but not for GRE Verbal and GRE Analytical Writing. Ragosta and Nemceff ( 1982 ) reported on the differences in the performance of D/HH and non-disabled students on SAT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to predictive bias (i.e., differential prediction), several studies have concluded that predictive bias does not appear to be an issue using the GRE. For example, Ling and colleagues (2020) examined differential prediction between students without reported disabilities, students with reported disabilities who received accommodations, and students with reported disabilities who did not receive accommodations. Although they ultimately relied on a relatively small sample of students with disabilities ( n s = 103 and 283), the researchers found only minimal evidence of differential prediction between students without disabilities and students with disabilities (with or without accommodation); the differential prediction varied across disability subtype ranging from none to minimal.…”
Section: Part 2: Critically Evaluating Alternatives To the Grementioning
confidence: 99%